(untitled) (Jurnal Manajemen Bisnis, 2022)
The purpose of this study is to analyze and investigate the relationship between country of origin and brand variables on consumer attitudes. The sample selection used a student sample from ITB Nobel Indonesia students, totaling 343 samples. The results of the study state that the country of origin has a positive and significant effect on consumer attitudes, as well as brands which also have a positive and significant effect on consumer attitudes.